2013
DOI: 10.3892/ol.2013.1437
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor-targeted lidamycin inhibits growth and metastasis of colon carcinoma

Abstract: Colon cancer is the third most common cancer in the world. The overexpression of tissue factor (TF) in colon cancer cells makes it an ideal target for colon cancer therapy. The purpose of the present study was to develop a TF-targeting energized fusion protein, mlFVII-LDP-AE, which is composed of a mouse Factor VII light chain (mlFVII) as the targeting domain conjugated to the highly cytotoxic antibiotic lidamycin (LDM, LDP-AE) as the effector domain. The potential efficacy of mlFVII-LDP-AE for mouse colon can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Circulating tumor and host‐derived tissue factor (TF) has been identified as an important link between cancer and thrombosis and TF expression has been reported in colon 26 cell lines . We therefore examined the contribution of circulating TF activity to our results and found that specifically blocking tissue factor in plasma from sham control, cachectic and non‐cachectic mice had no effect on thrombin generation under our conditions, suggesting the observed hypercoagulability was secondary to other factors.…”
Section: Discussionmentioning
confidence: 87%
“…Circulating tumor and host‐derived tissue factor (TF) has been identified as an important link between cancer and thrombosis and TF expression has been reported in colon 26 cell lines . We therefore examined the contribution of circulating TF activity to our results and found that specifically blocking tissue factor in plasma from sham control, cachectic and non‐cachectic mice had no effect on thrombin generation under our conditions, suggesting the observed hypercoagulability was secondary to other factors.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we chose mlFVII as the target-binding domain of the TF-CAR. Because mFVII possesses equivalent affinity to mTF and hTF [ 23 , 24 ], the TF-CAR T cells could attack both hTF-expressing tumor cells and mTF-expressing normal tissues in our mouse models; therefore, this system can stimulate the behavior of TF-CAR T cells with hlFVII as the target vehicle in the human body to a certain extent. Our data showed that after 3 infusions of TF-CAR T cells, no obvious pathological changes were detected in the important organs of the mice, such as the heart, liver, spleen, lung and kidney (Figure 8C ).…”
Section: Discussionmentioning
confidence: 99%
“…Others and we have previously shown that the light chain of FVII retained the affinity of original FVII to its receptor TF [ 21 , 22 ]. The light chains of the human and mouse FVII-conjugated drugs (hlFVII-LDM, mlFVII-LDM) that we developed showed effective growth suppression of TF-positive human lung cancer and mouse colon cancer, respectively [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%